Analisis Laporan Keuangan Laba Rugi Pada Usaha Penjualan Pupuk Kelompok Tani di Desa Purwoadi 19 A - Farhah Miftahussifa; Firda Sarachehan; Rehan Saputra; Risma Nur Khasanah; Carmidah Carmidah (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aims to analyze the profit and loss distribution mechanism in the Aida Jaya curtain joint venture with Marti convection, analyze the influence of financial performance on profit and loss distribution, and analyze the contribution of mature parties who influence the distribution of profit and loss. This study used descriptive qualitative method. The research results show that: (1) Profit and loss distribution is carried out with a ratio of 7:3 according to the initial capital of each party; (2). Financial performance does not affect the sharing ratio, but does affect the amount of profit or loss that is shared, (3) Contribute to the content of Aida Jaya Gorden in the form of production facilities and Konveksi Marti which provides production personnel, which greatly influences the success of this joint venture. This means you can use shared media to share your thoughts with others who already have large joint ventures.